The Effect of Workload on ATC’s Performance at Makassar Air Traffic Service Centre by Using Work Satisfaction and Work Stress as Intervening Variables - Nugraha, Andre Putra; Haerani, Siti (YUME : Journal of Management, 2023)
The prosperity and enduring sustainability of a company are intrinsically connected to the role and efficacy of its employees, as evaluated by the caliber of their work. In addition, the extent of tasks achieved and the timeliness of task completion can enhance performance and contribute to the achievement of organizational goals. The aim of this study is to assess the influence of workload on the performance of air traffic control (ATC), with work stress and job satisfaction acting as mediating factors. This study utilizes a quantitative methodology to investigate the cause-and-effect relationship between variables and assess the concept of their interconnectedness. A survey was conducted by distributing questionnaires to 100 participants, and the gathered data was analyzed using the SmartPLS 4 software. The data analysis indicates that work stress is positively and significantly correlated with ATC officer workload, although workload negatively impacts ATC performance and job satisfaction, but this influence is not statistically significant. More tasks mean weaker ATC performance. The path coefficient and p-value of this investigation are -0.004. With a path coefficient of -0.114 and a p-value larger than 0.05, work stress has a small effect on performance. A favorable and substantial link exists between job happiness and ATC officer performance (path coefficient = 0.841, p-value < 0.05). Work stress still mediates little structurally. This is compared to job happiness, which is high and strongly mediates workload on ATC performance. Keywords : workload; work stress; work satisfaction; air traffic controller; performance